Important trace element concentrations in ovine liver as determined by energy dispersive handheld X-ray fluorescence spectrometry - Botha, C.J. (Christoffel Jacobus) (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2016.